Now you know extreme weather [electronic resource] - Lennox, Doug (Canadian electronic library. Books collection, 2007)
Extreme weather such as that thought to come from global warming, hurricanes, tornadoes and melting permafrost concern us all. This work presents a compendium of questions and answers that enables you